EVOLUTION OF SURFACE AREA OF CLAY TREATED WITH SULPHUROUS ACID AND ITS SUBSEQUENT ACTIVATION: Short Communications - Okieimen, C O; Okieimen, F E; Aluyab, A O (Biological Sciences - PJSIR, 2001)
Clay sample (composition : Alp3 23.6%, Si02 52.9%, CaO 0.24%, Kp 0.05%, Nap 0.07%, Fep3 6.3%) was mixed with water and treated with various amounts of sulphur dioxide gas generated by reacting known amounts of sodium sulphite with dilute hydrochloric acid. The value of Fep3 in the clay sample was reduced by as much as 95% by the S02 treatment. The surface area of the clay sample was treated with S02 and subsequently activated (boiled in 0.8M HN03 and heated at 573°K).It was observed that treatment with S02 markedly enhanced the surface area of the clay samples, the surface area values of clay samples were compared with untreated clay samples and silica-alumina gels of comparable silica/alumina ratios